O direito humano de acesso universal à energia elétrica à luz do ODS no 7 da Agenda 2030 da ONU e da Lei no 14.300/2020 - Mário Paulo Machado Lemes Botta Nomoto (2024)
NOMOTO, Mário Paulo Machado Lemes Botta. The human right of universal access to clean electrical energy in the perspective of SDG 7 of the UN 2030 Agenda and Law 14,300/2020. 2024. 150 p. Dissertation (Master’s in Law) – Law School, Federal University of Mato Grosso do Sul, Campo Grande, 2024. Human rights refer to the quality of life of individuals and must be guaranteed by the State. Art. 6th of CF/88 defines a series of social rights, the right to energy does not appear on this list. PEC 44/2017, archived, was processed in the Federal Senate and aimed to raise the status of the need for electrical energy to guarantee its supply throughout the Brazilian territory. Access to electrical energy is of fundamental importance to guarantee human dignity as it enables the use and access to various goods and services. The UN Agenda 2030 foresees “Clean and affordable energy” as SDG 7 to “guarantee access to reliable, sustainable and modern energy sources for all”. In turn, Law 14,300/2022 established the legal framework for microgeneration and distributed minigeneration, the Electric Energy Compensation System, and the Social Renewable Energy Program. This program aimed to regulate access to clean energy for low-income populations. In effect, this Master's thesis explored the theme relating to the human right of universal access to clean electrical energy in light of SDG 7 of the UN Agenda 2030 and Law 14,300/2020 to answer the following question: What is the treatment given by the Brazilian legal system to promote universal access of the human right to electrical energy from renewable sources, especially for the needy population? To this end, its specific objectives were to analyze international legislation regarding electrical energy from renewable sources; analyze Brazilian legislation regarding clean electrical energy; find out whether SDG 7 and the respective goals of the UN 2030 agenda are being pursued and implemented, respectively, by the Brazilian state; describe the difficulties faced in accessing clean energy for the needy population; and learn about the sustainable renewable energy program (PERS) of Law 14,300/2022. In order to achieve these objectives and respond to the problem raised, the theoretical and methodological approach is dogmatic and axiological, the method is deductive, and the research is exploratory and descriptive with critical, documentary, and bibliographic analysis. Keywords: Human rights. Clean electrical energy. Sustainable Development Goal (SDG). UN 2030 Agenda. Law 14.300/2020.